Pengaruh Atribut Objek Wisata Alam, Promosi dan Karakteristik Individu terhadap Image Konsumen dan Pengambilan Keputusan Berkunjung (Studi Empiris terhadap Perilaku Wisatawan pada Objek Wisata Alam di Jatim) - Sudarmiatin, Sudarmiatin (Universitas Brawijaya, Indonesia, 2008)
The role of consumers is very significant for the business in gaining their purpose. The evident has proved that how the best of goods and services depend on the consumers awareness. That's why the rational reason of producing of goods and services are the existence of consumer's needs. The business have tried to afford the huge amount of promotion in order to encourage the buying decision of consumers. The purpose of the research is to examine and analyze: (1) the influence of attribute of natural tourism object on consumer's image and the decision in visiting; (2) the influence of promotion on consumers image and the consumer's decision in visiting; (3 the influence of individual characteristics on consumer's image and the consumer s decision in visiting: (4) the influence of consumer's image on consumers decision in visiting; (5) the difference attribute of natural tourism object, promotion, individual characteristic, consumer's image and the consumer's decision in visiting at 4 various groups attractions of natural tourism object in East Java. The population is 220 national tourist who are visiting in weekend at 16 natural tourism object in East Java and 200 questionnairs considered to analyze. Sampling method is by multistage sampling which consisted of proporsioned purposive sampling and accidental sampling. Data analyze is applied by descriptive and inferential statistics. Descriptive analyze is done by percentage and inferential analyze is done by SEM through AMOS Software 4.01 verse and ANOVA through LSD. The analyze has indicated that (1) there is positive and significant influence between attribute of natural tourism object on consumers image and consumer s desiocion in visiting; (2) there is not influence of promotion on consumer's image and the consumer's decision in visiting; (3) there is positive and significant influence between individual characteristics on consumer's image and the consumers decision in visiting; (4) there is positive and significant influence between consumer's image on the consumer's decision in visiting; (5) there is significant difference of attribute of natural tourism object, promotion and the consumer's decision in visiting at 4 various groups attractions of natural tourism object in East Java.